INVESTIGATION OF THERMAL CONDUCTIVITY OF LUFFA AND LUFFA-COIR REINFORCED EPOXY COMPOSITES - Anbukarasi, K.; Hussain, S. Imran; Kalaiselvam, S. (International Journal of Research -GRANTHAALAYAH, 2020)
Thermal behavior of luffa and coir reinforced epoxy composites have been evaluated for a constant total fiber volume fraction 0.4Vf by varying the ratio of luffa and coir fiber. Thermal conductivity of luffa-epoxy and luffa-coir reinforced epoxy composite was studied experimentally and analytically in terms of fiber size and fiber volume. Thermal conductivity of composites was investigated experimentally by a guarded heat flow meter method. The experimental results at different volume fraction were compared with three theoretical models. The composite C has the lowest thermal conductivity of 0.206 W/mk with 0.81 % of voids. The experimental values of thermal conductivity of hybrid composites are the good correlation with the Maxwell and Maxwell-Eucken models. As in a case of 0.4 Vf of luffa-epoxy composites these values are closer to the rule of mixture models. The thermal stability of the composites was investigated by thermogravimetric analysis. This result reveals that the hybridization of luffa and coir with epoxy allows a significantly improved insulation ability of the composites.